2021
DOI: 10.1136/bmjopen-2020-044059
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ and healthcare professionals’ beliefs, perceptions and needs towards chronic kidney disease self-management in China: a qualitative study

Abstract: ObjectivesTo support the adaptation and translation of an evidence-based chronic kidney disease (CKD) self-management intervention to the Chinese context, we examined the beliefs, perceptions and needs of Chinese patients with CKD and healthcare professionals (HCPs) towards CKD self-management.DesignA basic interpretive, cross-sectional qualitative study comprising semistructured interviews and observations.SettingOne major tertiary referral hospital in Henan province, China.Participants11 adults with a diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 66 publications
0
4
0
2
Order By: Relevance
“…However, this conceptualization of personal control as the performance of coping behaviors may not be aligned with CKD patient perceptions based on the wording of items. For example, the item “My actions will have no effect on the outcome of my kidney disease” may be interpreted differently or more broadly than just the concept of coping behaviors, including other factors such as treatment adherence (e.g., diet) and performance/avoidance of risky behaviors (e.g., cigarette smoking) [ 13 ]. Since most CKD patients experience a gradual decline in kidney function and may have received information from their healthcare providers to expect that illness pattern, they may have a different interpretation of the meaning of “my actions” or “outcome” with respect to their CKD than the IPQ-R authors intended.…”
Section: Discussionmentioning
confidence: 99%
“…However, this conceptualization of personal control as the performance of coping behaviors may not be aligned with CKD patient perceptions based on the wording of items. For example, the item “My actions will have no effect on the outcome of my kidney disease” may be interpreted differently or more broadly than just the concept of coping behaviors, including other factors such as treatment adherence (e.g., diet) and performance/avoidance of risky behaviors (e.g., cigarette smoking) [ 13 ]. Since most CKD patients experience a gradual decline in kidney function and may have received information from their healthcare providers to expect that illness pattern, they may have a different interpretation of the meaning of “my actions” or “outcome” with respect to their CKD than the IPQ-R authors intended.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis and systematic review of self-management interventions for CKD found that self-management (e.g., lifestyle modifications such as for nutrition and physical exercise, and/or medical behaviour modifications such as treatment adherence and complication control) can lead to lower blood pressure, C-reactive protein, and glycated haemoglobin (HbA1c) levels in CKD patients [48]. Despite the reported benefits, self-management is poorly understood by patients and physicians [49] and each has frequently cited lack of CKD knowledge and difficulties in making necessary lifestyle changes as barriers to effective self-management [49]. The Chinese practices Tai Chi and Qigong have been independently found to improve modifiable CKD risk factors (e.g., hypertension) [50, 51], suggesting their incorporation into a self-management programme may benefit some patients.…”
Section: Current and Recommended Strategies To Improve Prevention Dia...mentioning
confidence: 99%
“…Kehadiran gejala kronis, pendidikan pasien dan pengalaman belajar dari pasien lain berkontribusi pada keyakinan ini. Mereka sebagian besar mengatakan takut saat pertama kali didiagnosa penyakit ini karena mereka tahu bahwa tidak ada pengobatan yang dapat menyembuhkan penyakit mereka (Shen, et al, 2021). Hasil penelitian dari Muscat, et al, (2021) didapatkan bahwa tingkat distress penderita CKD berada pada tingkat sedang dan berat.…”
Section: Pembahasanunclassified